TREATMENT OF ANORECTAL PARAKS IN NEWBORNS AND PREVENTION OF COMPLICATIONS (World Bulletin of Public Health, 2024)
Anorectal malformations are one of the most common birth defects in pediatric coloproctology, "occurring on average in one in every 5,000 newborns". The coverage of anatomical types of this defect is characterized by a wide and varied nature, in which they can range from imperceptible deviations to complex anomalies, as well as require treatment in a modern way. More than half of children with anorectal malformations may also have other developmental disabilities, making it difficult to choose the optimal treatment tactics as well as affecting a significant increase in the number of risk factors leading to negative outcomes
Keywords: internal hernias; neonatal surgery; transabdominal ultrasound examination